Personal Audiovisual Aptitude Influences the Interaction Between Landscape and Soundscape Appraisal - Sun, Kang; Echevarria Sanchez, Gemma M.; De Coensel, Bert; Van Renterghem, Timothy; Talsma, Durk; Botteldooren, Dick (Frontiers in Psychology, 2018)
It has been established that there is an interaction between audition and vision in the appraisal of our living environment, and that this appraisal is influenced by personal factors. Here, we test the hypothesis that audiovisual aptitude influences appraisal of our sonic and visual environment. To measure audiovisual aptitude, an auditory deviant detection experiment was conducted in an ecologically valid and complex context. This experiment allows us to distinguish between accurate and less accurate listeners. Additionally, it allows to distinguish between participants that are easily visually distracted and those who are not. To do so, two previously conducted laboratory experiments were re-analyzed. The first experiment focuses on self-reported noise annoyance in a living room context, whereas the second experiment focuses on the perceived pleasantness of using outdoor public spaces. In the first experiment, the influence of visibility of vegetation on self-reported noise annoyance was modified by audiovisual aptitude. In the second one, it was found that the overall appraisal of walking across a bridge is influenced by audiovisual aptitude, in particular when a visually intrusive noise barrier is used to reduce highway traffic noise levels. We conclude that audiovisual aptitude may affect the appraisal of the living environment.